ANALISIS ELEMEN-ELEMEN FRAUD PENTAGON SEBAGAI DETERMINAN FRAUDULENT FINANCIAL REPORTING - Khusnatul Zulfa; Amira Bayagub (Universitas Pamulang, 2018)
AbstractThis study aims to examine the influence of externalxpressure, institutionalownership, xfinancial stability, xquality of external auditor, xchange inxauditor, change in director and frequentxnumber of CEO’s picture on the fraudulent financial reporting among the property and real estate firms listed in Indonesia stock exchange during 2014-2016. The data used in this study is secondary data obtained from the firms’ annual report which was accessed through www.idx.co.id. The data analysis method used in this study is multiple linear regression analysis. SPSS ver 2.0 was used to analyze the data. The samples were selected using a non-probability sampling technique with a purposive sampling method and obtained a sample of 41 property and real estate companies during 2014-2016. The results of variable test indicates that external pressure and change in director partially influences fraudulent financial reporting, while institutional ownership, financial stability, quality of external auditor, change in auditor, and frequent number of CEO’s picture partially does not influence fraudulent financial reporting. The Simultaneous test shows that external pressure, institutional ownership, financial stability, quality of external auditor, change in auditor, change in director and frequent number of CEO’s picture Keywords: External Pressure, Institutional Ownership, Financial Stability, Quality of External Auditor, Change in Auditor, Change in Director, Frequent Number of CEO’s Picture, Fraudulent Financial Reporting.